Idosas que moram sozinhas: a construção da rede de relacionamento, apoio e cuidado - Wanderley, érica Maria Tenório (2016)
In Brazil, the expectation of the people's living 60 years or more has increased, from this reality, we highlight the amount of homes formed by older who are single and living alone. Starting from the perspective that the support of a relational system is of great importance as it provides exchanges, support and protection, it must be recognized that the more the subject age, tends to have limitations which cause them to depend on others, are family, friends or paid professionals. Against this background, it appears that the reality of elderly who do not have children and spouses, and inhabiting a one-person household, is little known, especially in the state of Pernambuco. Based on these, the general objective of this research was to describe as the elderly, who are not married and have no children, build their networks in order to support and care. The specific objectives were to identify the sociodemographic profile of them; analyze how they perceive their aging process; and identify their needs and feelings about the fact of living alone and their expectations for the future and the reasons that led them to live alone. It is a qualitative research, which was attended by eight elderly women with chronological age of 60, unmarried and living alone. The instrument used was an interview consists of questions that met the research objectives and also to the socio-demographic data of the participants. The interviews were analyzed according to the technique of thematic content analysis. The main results showed: 1) the heterogeneity of aging, since older emphasized the importance of having a proper lifestyle that provides autonomy and satisfaction with life; 2) the construction of social networking, support and care in the family has the primary source (especially brothers and nephews), followed by spirituality / religiosity and friendships; 3) income, combined with a good education, appeared as providing security and independence; 4) the experience of living alone, in general, was viewed positively because the elderly live to old age soon, satisfactory health and occupations. It is hoped that the research contributes to knowledge about the reality of these older, as can also support the work of the professionals that they meet or are interested in aging theme.